2018
DOI: 10.1080/13803395.2018.1510904
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and implicit memory for music in healthy older adults and patients with mild Alzheimer’s disease

Abstract: The results have implications for memory interventions for patients with mild AD. The implicit memory findings suggest that patients with AD may still show a preference for information familiar to them. The explicit memory results support prior findings that patients with AD rely heavily on familiarity, but also suggest that there may be limitations on the benefits that music can provide to recognition memory performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
3
9
0
Order By: Relevance
“…Besides massive episodic memory deficits, our results indicate that learning is still possible, and resilient in AD at a moderate to severe stage, as revealed through the modification of the sense of familiarity towards items. This learning seems to be modulated by the nature of the information: stronger for visual information (paintings), and auditory information (music), but weaker for verbal information (verses), which fits with the literature on learning in the early stages of AD [8,24,[35][36][37]. However, the fact that we deliberately chose to change the voices between the exposure sessions and the test session may explain the low scores regarding verses and suggest that SoF is mainly sustained by the encoding of perceptual characteristics of the exposed stimuli.…”
Section: Discussion For Studysupporting
confidence: 85%
See 1 more Smart Citation
“…Besides massive episodic memory deficits, our results indicate that learning is still possible, and resilient in AD at a moderate to severe stage, as revealed through the modification of the sense of familiarity towards items. This learning seems to be modulated by the nature of the information: stronger for visual information (paintings), and auditory information (music), but weaker for verbal information (verses), which fits with the literature on learning in the early stages of AD [8,24,[35][36][37]. However, the fact that we deliberately chose to change the voices between the exposure sessions and the test session may explain the low scores regarding verses and suggest that SoF is mainly sustained by the encoding of perceptual characteristics of the exposed stimuli.…”
Section: Discussion For Studysupporting
confidence: 85%
“…They found that the mere exposure effect was still normal, whereas recognition was impaired. These findings were confirmed more recently by Deason et al [8] using newly-exposed music pieces. In this study, familiarity, recognition, and preference were measured for novel songs through three presentations of the items.…”
Section: Introductionsupporting
confidence: 77%
“…Therefore, it is necessary to develop clinical trials that promote standardized protocols based on the stage of the disease, or the biopsychosocial skills that need to be worked on through music therapy [11], and that can be applied as a complementary tool. This can enable caregivers of patients diagnosed with AD to cope with symptoms of the disease, such as memory impairment, which interferes with their quality of life [28].…”
Section: -Discussionmentioning
confidence: 99%
“…Anosognosia, a form of metacognitive deficit, may vary in time of onset, but tends to worsen as AD progresses ( Geurten et al, 2021 ). Studies have demonstrated preserved implicit metacognition in persons with AD (e.g., Golby et al, 2005 ; Sabat, 2006 ; Deason et al, 2019 ; Geurten et al, 2021 ), although explicit metacognition becomes increasingly impaired. The relevant distinction, in this regard, is the ability to explicitly consciously recall or recognize, as opposed to implicitly coding and retrieving without conscious awareness, as evidenced by a change in behavior or performance as result of previous experience or exposure ( Sabat, 2006 ).…”
Section: Consciousness In Alzheimer’s Disease: Preserved Cognitions Emotions and Subjective Experiencementioning
confidence: 99%